Socialization concepts and educational management development to create muslim citizenship through private islamic schools in the Southern Border Provinces of Thailand - Chatthida Yukhong (2020)
© 2019 International Journal of Islamic Thought. All rights reserved. The socialization concept is a part of concept that causes the people or citizens to have the characteristics needed by the community or society. The school is an important institution of socialization through educational managements by creating a learning processes aimed at changing human behaviors and attitudes into the planned valuable and desirable directions. In addition, educational managements have created the foundations of ways of thinking, actions or interactions involving individuals and their societies. Therefore, if there is a proper education or socialization process, it will lead to quality of education and citizenship. This article originated from reviewing relevant documents by reviewing socialization concepts and educational management developments of Muslims through private Islamic schools in the southern border provinces of Thailand before 1961 until the present. It reflects the developments of socialization in order to create a Muslim citizenship and the socialization processes to be in line with the government educational management policies. But at the same time, the socialization processes also maintain the identity of the Muslims in Thailand.